Materials evaluation and design for language teaching - McGrath, Ian, 1945- (Edinburgh textbooks in applied linguistics., 2016)
"Since the first edition of this book was published in 2002 there have been many changes in language teaching, not least those associated with technological developments. Despite such changes, the same basic needs remain as far as teacher education is concerned. Teachers still need advice on how to: evaluate coursebooks and other core materials systematically; source and evaluate other materials; adapt materials; design their own materials; Materials Evaluation and Design for Language Teaching provides this - offering a systematic approach to the selection and subsequent evaluation of textbooks and practical advice on their adaptation and supplementation. For teachers who prefer to prepare their own materials there are suggestions on systematising the process of materials development and on the use of learner-generated materials."--Publisher's website